Reflective team in caring for people living with dementia: a base for care improvement. Issue 3 (4th May 2017) - Jonasson, Lise-Lotte; Nyström, Maria; Rydström, Ingela
Abstract: A reflective team (RT) is a team of professional carers who reflect on a specific caring issue under the direction of an RT leader. The goal for the reflective process is to accomplish care improvement based on research and proven experience, and the first step is to reflect upon the competence that already exists in the context in which RT takes place. This study aims to bring previous unarticulated competence in caring for people living with dementia to the surface after it has been reflected during RT sessions. Ten assistant nurses who work closely with patients who have dementia and attend RT sessions on a regular basis were interviewed about their competence for caring for people living with dementia. Using a phenomenographic analysis, two qualitatively separate categories emerged: general caring skills and dementia-specific caring skills. It was concluded that specific skills in caring for people living with dementia build in caring skills and that tacit knowledge can be explicit and be expressed when it has been reflected in RT.